2015
DOI: 10.1089/tmj.2014.0052
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Technology-Based Interventions to Maintain Weight Loss

Abstract: Based on the review, guidelines were established for the selection and potential success of technology-based WLMIs. The effectiveness of technology-based maintenance interventions for weight loss varied, and potential strategies and approaches are discussed to improve their effectiveness. Further studies are needed to better evaluate and refine the efficacy of technology-based WLMIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…It is even a well-known predictor for success. Stabilizing weight can be especially demanding due to diminishing positive external feedback [11, 20]. In the present evaluation, none of the intervention groups showed a decrease in their values of the subscale social pressure (mean WBI = +0.1, mean PMI = +0.2, p  = 0.546) during the self-monitoring phase.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…It is even a well-known predictor for success. Stabilizing weight can be especially demanding due to diminishing positive external feedback [11, 20]. In the present evaluation, none of the intervention groups showed a decrease in their values of the subscale social pressure (mean WBI = +0.1, mean PMI = +0.2, p  = 0.546) during the self-monitoring phase.…”
Section: Discussionmentioning
confidence: 48%
“…The gradual reduction of controlled treatment and the increase of autonomy are important in long-term follow-up support [11]. Studies of Statistics Austria call attention to new technological means with the potential to support tailored life style interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though little is known about maintenance effects and use of extended care strategies to support SSB behaviors, the weight loss literature provides some useful insight. The use of extended care is recommended to address the issue of maintenance [ 21 ]; however, a systematic review of the effectiveness of technology-based (internet, telephone and interactive television) weight-loss maintenance interventions found mixed results [ 23 ]. Overall, the review found technology based extended care was more effective than usual care, but not as effective as personal contact.…”
Section: Introductionmentioning
confidence: 99%
“…These computer- and web-based approaches make these educational tools accessible to a wide audience, disregarding geographical distances [13]. A recent review [14] of technology-based interventions to maintain weight loss concluded that such interventions are ‘most likely to be more effective than conventional care'. …”
Section: Introductionmentioning
confidence: 99%